1993
DOI: 10.1093/ajcn/58.3.343
|View full text |Cite
|
Sign up to set email alerts
|

Iron status and intake of older infants fed formula vs cow milk with cereal

Abstract: One hundred four infants were randomly assigned to receive whole cow milk plus iron-fortified cereal (WCM + C) in accord with the previous recommendations of the Committee of Nutrition/American Academy of Pediatrics (CON/AAP); one of two iron-fortified, follow-up formulas; or an iron-fortified infant formula. Mean iron intakes and vitamin C exceeded the recommended dietary allowance in all groups. By 12 mo of age, mean ferritin and mean corpuscular volume were lower in the WCM + C group and significantly more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
0
2

Year Published

1993
1993
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 18 publications
6
47
0
2
Order By: Relevance
“…Clearly iron status indices need to be interpreted with caution over the 6-24-month-old age range, as recently emphasised by others (Aggett et al, 2002). Nevertheless, an age-related decline in iron stores in this group of children is consistent with longitudinal and intervention studies, which generally show that ferritin levels decline across the 6-24 month age range when cows' milk or unfortified formula is fed, whereas they remain constant when children consume iron-fortified formula (Fuchs et al, 1993;Michaelsen et al, 1995;Daly et al, 1996;Gill et al, 1997;Oti-Boateng et al, 1998;Morely et al, 1999;Sherriff et al, 1999;Virtanen et al, 2001). It is also consistent with the observed dietary iron intakes in our study which were markedly lower in the 12-24 month than 6-11.9-month-old children (8.4 vs 4.6 mg/day) (Soh et al, 2001).…”
Section: Discussionsupporting
confidence: 62%
“…Clearly iron status indices need to be interpreted with caution over the 6-24-month-old age range, as recently emphasised by others (Aggett et al, 2002). Nevertheless, an age-related decline in iron stores in this group of children is consistent with longitudinal and intervention studies, which generally show that ferritin levels decline across the 6-24 month age range when cows' milk or unfortified formula is fed, whereas they remain constant when children consume iron-fortified formula (Fuchs et al, 1993;Michaelsen et al, 1995;Daly et al, 1996;Gill et al, 1997;Oti-Boateng et al, 1998;Morely et al, 1999;Sherriff et al, 1999;Virtanen et al, 2001). It is also consistent with the observed dietary iron intakes in our study which were markedly lower in the 12-24 month than 6-11.9-month-old children (8.4 vs 4.6 mg/day) (Soh et al, 2001).…”
Section: Discussionsupporting
confidence: 62%
“…The duration of cow's milk feeding in the first year has been associated negatively with iron status in other studies (Mills, 1990;Tunnessen & Oski, 1987). Tunnessen and Oski (1987) concluded that the main factor responsible for iron inadequacy in infants receiving cow's milk from 6 months of age was the low content of iron rather than gastrointestinal bleeding in infants caused by cow's milk proteins, which has been suggested elsewhere (Fuchs et al, 1993). The negative effect of cow's milk on iron status has also been attributed to its calcium content, as calcium has been shown to inhibit iron absorption in single meal studies (Cook et al, 1991;Hallberg et al, 1991), but whether the effect of calcium on iron absorption persists in a complete diet has been questioned (Reddy & Cook, 1997).…”
Section: Discussionmentioning
confidence: 71%
“…Infants who had either serum ferritin or MCV or both indices above these cut-off points were classified as not being iron-deficient. The cut-off value for Hb of 105 g=l has been used and deemed to be appropriate for this age group (Michaelsen et al, 1995;Siimes et al, 1984), as well as the cut-off value for MCV of 74 fl (Fuchs et al, 1993;Gill et al, 1997). The value for serum ferritin of 12 mg=l is according to WHO criteria (INACG et al, 1998;WHO, 2001).…”
Section: Food Recordsmentioning
confidence: 99%
See 1 more Smart Citation
“…The children were also divided into being iron-depleted or not, with SF below or above 12 mg/l. The cutoff value for Hb of 105 g/l has been used and deemed to be appropriate for infants (Siimes et al, 1984;Michaelsen et al, 1995), as well as the cutoff value for MCV of 74 fl for infants and young children (Hercberg et al, 1987;Fuchs et al, 1993;Gill et al, 1997) The value for SF of 12 mg/l is according to the WHO criteria (INACG et al, 1998;WHO, 2001). Since SF is a phase reactant, parents were urged not to bring their children to blood sampling if they were ill or had been ill the last couple of days, also an experienced paediatrician evaluated their health and CRP was measured when appropriate.…”
Section: Blood Samplesmentioning
confidence: 99%